Sensory Modulation Disorder (SMD) and Pain: A New Perspective - Bar-Shalita, Tami; Granovsky, Yelena; Parush, Shula; Weissman-Fogel, Irit (Frontiers in Integrative Neuroscience, 2019)
Sensory modulation disorder (SMD) affects sensory processing across single or multiple sensory systems. The sensory over-responsivity (SOR) subtype of SMD is manifested clinically as a condition in which non-painful stimuli are perceived as abnormally irritating, unpleasant, or even painful. Moreover, SOR interferes with participation in daily routines and activities, co-occurs with daily pain hyper-sensitivity, and reduces quality of life due to bodily pain. Laboratory behavioral studies have confirmed abnormal pain perception, as demonstrated by hyperalgesia and an enhanced lingering painful sensation, in children and adults with SMD. Advanced quantitative sensory testing has revealed the mechanisms of altered pain processing in SOR whereby despite the existence of normal peripheral sensory processing, there is enhanced facilitation of pain transmitting pathways along with preserved but delayed inhibitory pain modulation. These findings point to central nervous system involvement as the underlying mechanism of pain hypersensitivity in SOR. Based on the mutual central processing of both non-painful and painful sensory stimuli, we suggest shared mechanisms such as cortical hyper-excitation, an excitatory-inhibitory neuronal imbalance, and sensory modulation alterations. This is supported by novel findings indicating that SOR is a risk factor and comorbidity of chronic non-neuropathic pain disorders. This is the first review to summarize current empirical knowledge investigating SMD and pain, a sensory modality not yet part of the official SMD realm. We propose a neurophysiological mechanism-based model for the interrelation between pain and SMD. Embracing the pain domain could significantly contribute to the understanding of this condition’s pathogenesis and how it manifests in daily life, as well as suggesting the basis for future potential mechanism-based therapies.